2017
DOI: 10.3390/microorganisms5020034
|View full text |Cite
|
Sign up to set email alerts
|

Comment on: “Melanisation of Aspergillus terreus—Is Butyrolactone I Involved in the Regulation of Both DOPA and DHN Types of Pigments in Submerged Culture? Microorganisms 2017, 5, 22”

Abstract: A recent article by Palonen et al. describes the effect of butyrolactone I on the expression of a secondary metabolite biosynthesis gene cluster from Aspergillus terreus that shows similarities to fusarubin biosynthesis gene clusters from Fusarium species. The authors claim that two different types of pigments are formed in Aspergillus terreus conidia, whereby one pigment is termed a DOPA-type melanin and the second a DHN-type melanin. Unfortunately, the terminology of the classification of melanin-types requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
3
4
0
Order By: Relevance
“…Nevertheless, in all three treatments a classical growth pattern (lag-, log-, stationary- and death phase) was observed. Still the lag- and the stationary phase were not so pronounced in our experiments which could be explained by the weekly sampling intervals for CFU [50]. At the end of the experiment the CFU ranged between 502 (AP unt ) and 949 (AP dis ) in all treatments as it was similarly reported for sterilized and non-sterilized aquaponic lettuce production by Pantanella, Cardarelli [51].…”
Section: Discussionsupporting
confidence: 67%
“…Nevertheless, in all three treatments a classical growth pattern (lag-, log-, stationary- and death phase) was observed. Still the lag- and the stationary phase were not so pronounced in our experiments which could be explained by the weekly sampling intervals for CFU [50]. At the end of the experiment the CFU ranged between 502 (AP unt ) and 949 (AP dis ) in all treatments as it was similarly reported for sterilized and non-sterilized aquaponic lettuce production by Pantanella, Cardarelli [51].…”
Section: Discussionsupporting
confidence: 67%
“…We can accept that the properties of the pgm gene cluster to produce pigment are unconfirmed by biochemical methods. As pointed out by Geib and Brock [ 3 ], the observed similarity with the fusarubin gene cluster of the Fusarium fujikuroi may indicate sexual development during the growth conditions used in this study. This raises a question regarding the observed upregulation of one of the key regulators of asexual conidiation, abaA —occurring exactly at the same time point as the pgm cluster genes are upregulated as well [ 5 , 6 ].…”
supporting
confidence: 69%
“…Regarding the several further thoughts presented by Geib and Brock [ 3 ], we agree on the necessity to confirm them with further studies. In our previous study [ 4 ], we observed an increase in lovastatin production, both on the transcriptional and molecular level, and showed it to be enhanced already 24 h after butyrolactone I supplementation, 96 h prior to the speculated pgm cluster genes showed upregulation as described in our current study [ 5 ].…”
supporting
confidence: 69%
See 2 more Smart Citations